Achieving Low Yield Ratio in High‐Strength Steel by Tuning Multiple Microstructures. Issue 4 (28th October 2021) - Shi, Rongjian; Wang, Tengfei; Gao, Kewei; Wang, Zidong; Qiao, Lijie; Pang, Xiaolu
Abstract : Herein, martensite–ferrite dual‐phase high‐strength low‐alloy (HSLA) steels with a low yield ratio (YR), which is achieved through different heat‐treatment procedures, are evaluated in terms of multiple microstructures, e.g., grain size, soft‐phase proportion, and morphology. The extended austenitizing time exhibits a low YR by sacrificing both the yield and tensile strengths synchronously. By subtly regulating the tempering temperatures, the YR can be optimized from 0.93 to 0.89 after tempering at an applicable temperature. Moreover, by introducing the equivalent shape factor (ESF), the morphology effects of ferrite on the YR are investigated based on the microstructural observation and Abaqus finite element analysis. The YR is inversely proportional to the ESF of the microstructure, which can be used to guide the design of microstructural morphology. The correlation between the yield strength (YS), YR, and work hardening exponent is achieved using the Swift equation. The lower YR generates greater work hardening and reduced YS. By tuning multiple microstructures, high YS and relatively low YR are achieved via the secondary‐quenching intercritical heat treatment, which is beneficial for designing low‐yield‐ratio HSLA steels in industrial applications. Abstract : Design of a low yield ratio (YR) in ultrahigh yield strength (YS) high‐strength low‐alloy (HSLA) steels is crucial for safe applications. The YR is optimized by subtly regulating the grain refinement and soft ferrite proportion. Besides, the YR is inversely proportional to the equivalent shape factor of the morphology. The optimized YR (0.91) and YS (925 MPa) are acquired.